2013
DOI: 10.1002/ccd.25001
|View full text |Cite
|
Sign up to set email alerts
|

The myocardium supplied by a chronic total occlusion is a persistently ischemic zone

Abstract: In symptomatic patients, a CTO, even with regional left ventricular impairment and/or excellent collateral development, reveals an ischemic zone. This ischemic zone can be normalized by PCI with outcomes appearing to be comparable to non-CTO patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 23 publications
1
63
1
6
Order By: Relevance
“…Previous studies in that area using SPECT or fractional flow reserve (FFR) did not find any relation between these two parameters [9][10][11][12]22]. However, a study with transthoracic coronary Doppler echocardiography with venous adenosine infusion showed that collateral flow reserve correlates well with Rentrop graded collateral flow [23].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies in that area using SPECT or fractional flow reserve (FFR) did not find any relation between these two parameters [9][10][11][12]22]. However, a study with transthoracic coronary Doppler echocardiography with venous adenosine infusion showed that collateral flow reserve correlates well with Rentrop graded collateral flow [23].…”
Section: Discussionmentioning
confidence: 88%
“…The latter hypothesis is based on the observation that stress ischaemia in the CTO territory was found in all patients undergoing FFR, in around 80% of patients undergoing SPECT, and only in around 60% of patients in our study [9][10][11][12]22]. In one small study using CMR, stress perfusion deficits not matching the myocardial scar in patients with CTO were found in 11/16 patients (68%) [24].…”
Section: Discussionmentioning
confidence: 94%
“…Elegant studies have shown that virtually all CTOs are ischemic when tested by fractional fl ow reserve, regardless of the maturity of collateral channels (9,10). Most are ischemic at rest, even in the absence of vasodilators and hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…Well‐developed collateral circulation to the CTO target vessel distal to the occlusion has been used as an argument against CTO revascularization, despite studies demonstrating ischemia in nearly all such cases 12, 13. Jang et al10 examined the long‐term outcomes of different treatment strategies among 738 patients with at least one CTO lesion and well‐developed collateral channels.…”
Section: Clinical Benefitsmentioning
confidence: 99%